“Zindagi aik Naraz Matan”: A Postmodern Study - Dr. Naeema Bibi (دریافت)
Shahida Dilawar's novel “Zindagi aik naraz  Matan” was published in 2023 by Akas Publications Lahore, offers a unique exploration of contemporary social realities through the lens of postmodern literature. The narrative is intricately woven around three main characters include Anum (Anu), Ali (narrator) and Sarwar Javed highlighting the nuances of life spent in the complex landscape of modern offices. This paper delves into the postmodern nature of the novel, shedding light on the pervasive use of various postmodern techniques. Such as irony, playfulness,  black humour,   faction, like Metafiction, Historiographic  Metafiction, Pastiche, Intertextuality, Paranoia ،Temporal Distortion, Maximalism have been used repeatedly. In this paper, it is tried to understand the novel by studying these postmodern techniques.